Measuring urban mobility: methodological aspects of vehicle counting applied to Argentine cities - Grassi, Yamila Soledad; Diaz, Monica Fatima (LACCEI, 2025)
Urban mobility is crucial for community life in cities, as it facilitates movement between work, educational, recreational and commercial spaces; considering all the necessary journeys that people make using different means of transport. As the urban population grows, it becomes a challenge to adapt the development of the city to meet new mobility needs in a sustainable, inclusive and economical way. In this sense, one of the great goals is to balance these three pillars of sustainability, which requires a holistic approach in its study. This work aims to promote sustainable mobility through the development of methodologies for the collection of key data, such as vehicular flow and its characterization. The acquisition of these data allows the analysis of congestion, vehicle use trends, and estimation of pollutant emissions, facilitating the design of public policies and evidence-based decision-making. This study focuses on describing the methodology used in Bahía Blanca, Argentina, to perform manual vehicular flow counts and segmentation, by direct observation of videos at strategic points of the city. Ten-minute videos recorded during peak hours are used, and the data are extrapolated to one hour. The methodology has been applied in the micro and macro center of the city, as well as on university campuses, adapted to the objective of each study. This kind of research is pioneering in Bahía Blanca, with the purpose of assisting in the decision-making process of authorities. Finally, the methodology can be replicated in other cities, as long as it is adapted to the specific context.